Flight from safety: How a change to the deposit insurance limit affects households' portfolio allocation - H. Evren Damar; Reint E. Gropp; Adi Mordel (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2019)
We study how an increase to the deposit insurance limit affects households' portfolio allocation by exogenously reducing uninsured deposit balances. Using unique data that identifies insured versus uninsured deposits, along with detailed information on Canadian households' portfolio holdings, we show that households respond by drawing down deposits and shifting towards mutual funds and stocks. These outflows amount to 2.8% of outstanding bank deposits. The empirical evidence, consistent with a standard portfolio choice model that is modified to accommodate uninsured deposits, indicates that more generous deposit insurance coverage results in nontrivial adjustments to household portfolios.
urn:nbn:de:gbv:3:2-111164
Keywords: D14; G21; G28; L51; 330; deposit insurance; banking; households; regulation